Effectiveness of milk whey protein‐based ready‐to‐use therapeutic food in treatment of severe acute malnutrition in Malawian under‐5 children: a randomised, double‐blind, controlled non‐inferiority clinical trial. Issue 3 (13th February 2014) - Bahwere, Paluku; Banda, Theresa; Sadler, Kate; Nyirenda, Gertrude; Owino, Victor; Shaba, Bina; Dibari, Filippo; Collins, Steve
Abstract The cost of ready‐to‐use therapeutic food (RUTF) used in community‐based management of acute malnutrition has been a major obstacle to the scale up of this important child survival strategy. The current standard recipe for RUTF [peanut‐based RUTF (P‐RUTF)] is made from peanut paste, milk powder, oil, sugar, and minerals and vitamins. Milk powder forms about 30% of the ingredients and may represent over half the cost of the final product. The quality of whey protein concentrates 34% (WPC34) is similar to that of dried skimmed milk (DSM) used in the standard recipe and can be 25–33% cheaper. This blinded, parallel group, randomised, controlled non‐inferiority clinical trial tested the effectiveness in treating severe acute malnutrition (SAM) of a new RUTF formulation WPC‐RUTF in which WPC34 was used to replace DSM. Average weight gain (non‐inferiority margin Δ = −1.2 g kg−1 day−1) and recovery rate (Δ = −10%) were the primary outcomes, and length of stay (LOS) was the secondary outcome (Δ = +14 days). Both per‐protocol (PP) and intention‐to‐treat (ITT) analyses showed that WPC‐RUTF was not inferior to P‐RUTF for recovery rate [difference and its 95% confidence interval (CI) of 0.5% (95% CI –2.7, 3.7) in PP analysis and 0.6% (95% CI –5.2, 6.3) in ITT analysis] for average weight gain [0.2 (−0.5; 0.9) for both analyses] and LOS [−1.6 days (95% CI, −4.6, 1.4 days) in PP analysis and −1.9 days (95% CI, −4.6, 0.8 days) for ITT analysis]. In conclusion, whey protein‐based RUTF is an effective cheaper alternative to the standard milk‐based RUTF for the treatment of SAM.